Knowledge Level of DAESI and Non-DAESI Dealers for Paddy and Wheat Cultivation in Punjab (Indian Journal of Extension Education, 2022)
The study was conducted during 2020 in Ludhiana and Faridkot district of Punjab to know the knowledge level of DAESI (Diploma in Agricultural Extension Services for Input Dealers) and non-DAESI dealers about paddy and wheat cultivation in Punjab. From the study it was found that DAESI dealers had medium to high level of knowledge on wheat where non-DAESI dealers had medium to low level of knowledge. DAESI dealers had high level of knowledge on cultivation practices of paddy than non-DAESI dealers. In case of DAESI dealers, education, economic motivation, management orientation, decision making, mass media utilization and extension contact had positive and significant relationship with knowledge about cultivation practices of wheat and paddy. But only education had positive and significant relationship with knowledge about cultivation practices of wheat and paddy in non-DAESI dealers.